Safety and Efficacy of High-dose Daily Vitamin D3 Supplementation in Children and Young Adults With Sickle Cell Disease. Issue 5 (July 2015) - Dougherty, Kelly A.; Bertolaso, Chiara; Schall, Joan I.; Smith-Whitley, Kim; Stallings, Virginia A.
<x xml:space="preserve">Abstract</x> Suboptimal vitamin D (vit D) status (<32 ng/mL) is ubiquitous among African American children with type SS sickle cell disease (SCD-SS). The vit D supplemental dose to normalize vit D status is unknown. Five to 20-year-old African American children with (n=21) and without (n=23) SCD-SS were randomized to vit D3 supplementation (4000 or 7000 IU/d) and evaluated at 6 and 12 weeks for changes in vit D and SCD status. A dose was considered unsafe if serum calcium was elevated associated with elevated serum 25 hydroxyvitamin D (25(OH)D). At baseline 95% of subjects with SCD-SS and 87% of healthy controls had suboptimal vit D status (mean±SD, 19.2±7.2 and 22.3±9.3 ng/mL, respectively). After 12 weeks supplementation, both D3 doses were safe and well tolerated. Neither group achieved the a priori efficacy criterion of 25(OH)D≥32 ng/mL in >80% of subjects (45% in SCD-SS and 63% in controls). However, for both subjects with SCD-SS and healthy subjects by 12 weeks, deficient (<20 ng/mL) vit D status was eliminated only in those receiving 7000 IU/d. For subjects with SCD-SS, by 12 weeks there was a significant (all P<0.05) increase in fetal hemoglobin, decrease in high-sensitivity C-reactive protein, and reduction in the percentage of subjects with a high platelet count.